The modern school in the garbage settlement: different social imaginaries of the future of the Zabbaleen recycling school for boys - Abed El Fattah, Marwa Adel (AUC Knowledge Fountain, 2014)
At 9 am, when 11-year old Ezz starts his day at the Mukattam Recycling School, he is already quite exhausted. Like most Zabballeen or juvenile garbage-collectors, he was up until well into the night the day before, gathering trash with his father in the more affluent neighborhoods of Cairo. In its communication material, the NGO-based school he attends in the morning promises to turn Ezz and others like him into “waste-management entrepreneurs". Fueled by this goal along with illiteracy and basic mathematics classes, Ezz is expected to hand in a monthly quota of used shampoo bottles and miscellaneous beauty product containers manufactured by Procter and Gamble (P&G), the multinational funding this innovative school. As part of his school day, Ezz spends a couple of hours preparing P&G beauty product plastic containers for recycling. This recycling process dubbed the “Shampoo Program" by the school - is optional but also crucial for the children: the token pay they receive from the school depends on their participation in this activity. When he leaves school in the early afternoon, the second and longer part of Ezz's day begins. First, at home, he has to sort out the previous day's garbage collected with his father. The evening involves going back to the streets for a new round of trash hoarding. When I met him a year ago, Ezz was still a newcomer to the Recycling School and had hopes of becoming a doctor when he grew up. One year later (2013), he had a change of mind, informing me that he wants to keep on working with his father as a zabbal because it is such a “good job" like he said. This thesis focuses on the Recycling School students' life in terms of future, work, education and well-being.